1968
DOI: 10.1126/science.162.3853.570
|View full text |Cite
|
Sign up to set email alerts
|

Hurler and Hunter Syndromes: Mutual Correction of the Defect in Cultured Fibroblasts

Abstract: The biochemical defect of cultuired skin fibroblasts from Hurler or Hunter patients (faulty degradation of sulfated mucopolysaccharide, resulting in excessive intracellular accumulation) may be corrected if cells of these two genotypes are mixed with each other or with normal cells. The effect is mediated by substances released into the medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
170
0
1

Year Published

1974
1974
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 392 publications
(178 citation statements)
references
References 8 publications
5
170
0
1
Order By: Relevance
“…Correction of storage in neighboring cells occurs by endocytosis of secreted lysosomal enzymes from transduced cells. 20,21 Our studies in the MPSVII mouse have shown that the secreted GUSB can resolve lysosomal storage lesion in the brain at least 2 mm away from GUSB positively stained cells. 3,21 This shows that although enzyme was present in neighboring untransduced cells, it was below the level of histochemical detection.…”
Section: Aav In the Cat Brain Ch Vite Et Almentioning
confidence: 91%
See 1 more Smart Citation
“…Correction of storage in neighboring cells occurs by endocytosis of secreted lysosomal enzymes from transduced cells. 20,21 Our studies in the MPSVII mouse have shown that the secreted GUSB can resolve lysosomal storage lesion in the brain at least 2 mm away from GUSB positively stained cells. 3,21 This shows that although enzyme was present in neighboring untransduced cells, it was below the level of histochemical detection.…”
Section: Aav In the Cat Brain Ch Vite Et Almentioning
confidence: 91%
“…Since GUSB is a secreted enzyme that is endocytosed by neighboring untransduced cells, 20,21 we determined whether histochemically positive cells were cross-corrected or whether they expressed GUSB mRNA. In all …”
Section: In Situ Hybridizationmentioning
confidence: 99%
“…8 Moreover, NaGlu shares many properties with other lysosomal enzymes, which can be secreted and taken up by neighboring cells and transported to the lysosomes, resulting in broader distribution via a bystander effect. [9][10][11] Generally speaking, for MPS disorders, only 1-2% residual enzyme activity may be needed to normalize cell function. Therefore, it would not be necessary to transduce all cells for effective MPS IIIB treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In animal models, cells derived from human hematopoietic stem and progenitor cells can have widespread, nonhematopoietic tissue distribution (21). The engrafting cells remain hematopoietic (22,23) and can be present in many tissues, including nervous tissue, in the form of microglial cells and tissue macrophages and can provide the enzyme to neighboring affected cells (18), a concept recognized in tissue culture experiments in the 1960s (24).…”
Section: Inherited Metabolic Disordersmentioning
confidence: 99%